STUDY OF ANTI-INFLAMMATORY, ANTIPYRETIC AND ANALGESIC EFFECTS OF AZADIRACHTA INDICA LEAVES EXTRACT IN ALBINO RATS - ALYAS, S; ZAHRA, N; KHADAM, A; SULTANA, R; ZAHID, B; TARIQ, R; AKHTAR, R; RAFIQUE, HM; AHMAD, S (Biological and Clinical Sciences Research Journal, 2023)
An evergreen tropical tree known as neem (Azadirachta indica) has long been used in traditional medicine to various conditions, including fever, pain and inflammation. The prospective research aims to examine the analgesic, antipyretic and anti-inflammatory properties of the chloroform extract of A. indica. For this investigation, 108 albino rats weighing 160 to 200g each were employed. Carrageenan was used to induce paw edema to test the anti-inflammatory activity. Yeast was used to induce pyrexia to test the anti-pyretic activity. Finally, acetic acid induced abdominal writhing in rats to test the analgesic action. The chloroform extract was injected into the abdominal muscle and intraperitoneal tissue. The largest percentage of anti-inflammatory action that chloroform leaf extract could suppress was 53%. The maximal percentage inhibition of leaf extract against fever in terms of antipyretic efficacy was 90%. The highest percentage of inhibition against pain during analgesic activity was 56%. When compared to the common medications diclofenac and paracetamol substantial outcomes were seen in the anti-inflammatory, antipyretic and analgesic actions at 400 mg/kg, respectively. Fever, pain and inflammation all decreased significantly (p≤ 0.05). As a result, chloroform leaf extract from A. indica can be utilized as a potent medication to treat fever, pain (discomfort) and inflammation.